Online marketing to investors : how to develop effective investor relations - Valentine, Daniel R. (Finance and financial management collection., 2015)
This book introduces the online marketing and disclosure techniques which enable listed corporations to engage effectively with financial markets. These techniques are part of the discipline of Investor Relations (IR) which is the corporate function responsible for advising the senior officers of a listed company on the relationship between the company and the market for corporate stock. As a corporate function, IR is very young in the United Kingdom, but since the 1980s, it has rapidly penetrated the highest levels of corporate management as its value becomes clearer. The marketing of corporate stock is a key part of the value of effective IR, although the highly regulated nature of the world's leading stock markets means that a specialized form of marketing is required. Digital channels present great but underutilized potential to contribute to ever more effective IR. Online platforms offer fast, comprehensive, economical, flexible, and regulation-compliant methods of disclosing corporate information to investors, analysts, and other relevant parties in the investment evaluation and decision-making process. This book examines the ways in which digital mechanisms can facilitate the building of transparent, mutually-beneficial, and lasting relationships between companies and the investors and financial analysts that comprise the U.K. equity markets, using both established and emerging channels and technology, within the constraints of the U.K. regulatory context and customs of the equity markets. The problems with using "social media" in particular for disclosure are discussed, and a number of risks connected with use of the new media are explored. The book concludes by summarizing the key challenges facing investor marketing in the next decade.